A Novel Nitrogen Ion Implantation Technique for Turning Thin Film “Normally On” AlGaN/GaN Transistor into “Normally Off” Using TCAD Simulation - Gene Sheu (MDPI AG, 2021)
This study presents an innovative, low-cost, mass-manufacturable ion implantation technique for converting thin film normally on AlGaN/GaN devices into normally off ones. Through TCAD (Technology Computer-Aided Design) simulations, we converted a calibrated normally on transistor into a normally off AlGaN/GaN transistor grown on a silicon <111> substrate using a nitrogen ion implantation energy of 300 keV, which shifted the bandgap from below to above the Fermi level. In addition, the threshold voltage (Vth) was adjusted by altering the nitrogen ion implantation dose. The normally off AlGaN/GaN device exhibited a breakdown voltage of 127.4 V at room temperature because of impact ionization, which showed a positive temperature coefficient of 3 × 10−3 K−1. In this study, the normally off AlGaN/GaN device exhibited an average drain current gain of 45.3%, which was confirmed through an analysis of transfer characteristics by changing the gate-to-source ramping. Accordingly, the proposed technique enabled the successful simulation of a 100-µm-wide device that can generate a saturation drain current of 1.4 A/mm at a gate-to-source voltage of 4 V, with a mobility of 1487 cm2V−1s−1. The advantages of the proposed technique are summarized herein in terms of processing and performance.